2014
DOI: 10.4209/aaqr.2013.07.0259
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Performance of Statistical Models for Predicting PM10 Concentrations

Abstract: The ability to accurately model and predict the ambient concentration of Particulate Matter (PM) is essential for effective air quality management and policies development. Various statistical approaches exist for modelling air pollutant levels. In this paper, several approaches including linear, non-linear, and machine learning methods are evaluated for the prediction of urban PM 10 concentrations in the City of Makkah, Saudi Arabia. The models employed are Multiple Linear Regression Model (MLRM), Quantile Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 47 publications
(64 reference statements)
0
63
0
4
Order By: Relevance
“…Litle diference was observed between the two models, suggesting that the simpler MLR method was a beter option than GLM in that case. Studies in other locales have reported that PM 10 was normally distributed [26] or that PM 10 concentrations were right skewed [14]. Studies have found that the use of curvilinear transformations of input variables e.g.…”
Section: Regression Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Litle diference was observed between the two models, suggesting that the simpler MLR method was a beter option than GLM in that case. Studies in other locales have reported that PM 10 was normally distributed [26] or that PM 10 concentrations were right skewed [14]. Studies have found that the use of curvilinear transformations of input variables e.g.…”
Section: Regression Methodsmentioning
confidence: 99%
“…QR has been used very litle for modelling pollutants. One study that compared models developed using QR with MLR found that QR was beter at predicting hourly PM 10 concentrations [14].…”
Section: Regression Methodsmentioning
confidence: 99%
See 3 more Smart Citations